2018
DOI: 10.1002/minf.201800037
|View full text |Cite
|
Sign up to set email alerts
|

COX Inhibition Profiles and Molecular Docking Studies of the Lignan Hinokinin and Some Synthetic Derivatives

Abstract: Encouraged by the anti-inflammatory activity of hinokinin in vivo, which is also observed for the analogues dinitrohinokinin and diidrocubebin, herein we used in vitro and in silico methods to assess their selectivity profiles and predict their binding modes with Cyclooxygenases (COX-1 and 2). The in vitro assays demonstrated dinitrohinokinin is about 13 times more selective for COX-2 than for COX-1, a similar profile observed for the drugs celecoxib (selective index ≈9) and meloxicam (selective index ≈11). Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The results indicate that this compound is able to produce both central and peripheral effects. In terms of the mechanism of action, it has been demonstrated by in vitro assays that hinokinin and synthetic derivatives selectively inhibit COX-1 and COX-2 [34][35][36]. Furthermore, previous studies have reported that this compound has antitumoral, anti-inflammatory, antimicrobial and anti-trypanosomal activity [34].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that this compound is able to produce both central and peripheral effects. In terms of the mechanism of action, it has been demonstrated by in vitro assays that hinokinin and synthetic derivatives selectively inhibit COX-1 and COX-2 [34][35][36]. Furthermore, previous studies have reported that this compound has antitumoral, anti-inflammatory, antimicrobial and anti-trypanosomal activity [34].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the review on the effect of S. marianum in metabolic syndrome on both animal models and clinical trials conducted on humans suggested that silymarin has potential to be an alternative choice for treatment of metabolic syndrome disease [18]. Plants are primary source of compounds that inhibit these key enzymes during inflammation process by acting as natural inhibitors [19,20]. Multiple biotic as well as abiotic elicitors have previously been employed in vitro in several medicinal plant species to increase the content of secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Supporting information files include the synthetic procedure for pyrazole-enaminones 5 and molecular docking studies on 3D structures of COX-1 and COX-2 enzymes. 1 H, 13 C, 19 F NMR experiments, X-ray diffraction spectra and Mass spectra data of compounds 5 g-k were also added.…”
Section: Resultsmentioning
confidence: 99%
“…According to the redocking results, the configuration used in this study is a good model for predicting the interaction between receptor and target, because the root-mean-square deviation values obtained for COX-1 and COX-2 (0.85 Å and 0.69 Å, respectively (see Figure S1 in the Supporting Information) were less than 2.0 Å. [19] Regarding docking results for COX-1 and COX-2, Figure 4 shows that compound 5 g binds to the same site as celecoxib, interacting mainly by hydrophobic interactions (π-σ, π-alkyl, and alkyl-alkyl) with the COX-1 and COX-2 amino acid residues, and the 5-methyl-3-(trifluoromethyl)-pyrazole moiety and the morpholinyl group play an important role in this sense. In the COX-1, the following interactions occurred: the pyrazole moiety of compound 5 g with Val349 and Leu531; the trifluoromethyl group with the Val349, Ile345, and Leu359; the methyl with Val116 and Leu531; and the morpholinyl with the Val349 and Leu352 residue ( Figure 4A).…”
Section: Sar and Docking Studiesmentioning
confidence: 87%